The effect of brief mindfulness training on the micro-structure of human free-operant responding: Mindfulness affects stimulus-driven responding - Xiaosheng Chen (Journal of Behavior Therapy and Experimental Psychiatry, 2022)
Background and objectivesThe current study examines the extent to which mindfulness impacts on operant conditioning processes, and explores the suggestion that mindfulness training serves to make humans more sensitive to the current reinforcement contingencies with which they are presented. In particular, the effect of mindfulness on the micro-structure of human schedule performance was explored. It was expected that mindfulness might impact bout-initiation responding to a greater degree than within-bout responding, premised on the assumption that bout-initiation responses are habitual and not under conscious control, but within-bout responses are goal-directed and conscious.MethodsNonclinical participants experienced one of three brief (15min) interventions: focused attention breathing exercise (mindfulness), an unfocused attention breathing exercises, or no intervention. They then responded on a multiple random ratio (RR) random interval (RI) schedule.ResultsIn the no intervention and unfocused attention groups, overall and within-bout response rates were higher on the RR than the RI schedule, but bout-initiation rates were the same on the two schedules. However, for the mindfulness groups all forms of responding were higher for the RR than the RI schedule. Previous work has noted that habitual, and/or unconscious or fringe-conscious events, are impacted by mindfulness training.LimitationsA nonclinical sample may limit generality.ConclusionsThe current pattern of results suggests that this is also true in schedule-controlled performance, and offers an insight into the manner in which mindfulness alongside conditioning-based interventions, to bring all responses under conscious control.